2001
DOI: 10.1042/0264-6021:3590035
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of unique amphipathic antimicrobial peptides from venom of the scorpion Pandinus imperator

Abstract: Two novel antimicrobial peptides have been identified and characterized from venom of the African scorpion Pandinus imperator. The peptides, designated pandinin 1 and 2, are alpha-helical polycationic peptides, with pandinin 1 belonging to the group of antibacterial peptides previously described from scorpions, frogs and insects, and pandinin 2 to the group of short magainin-type helical peptides from frogs. Both peptides demonstrated high antimicrobial activity against a range of Gram-positive bacteria (2.4-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 49 publications
4
61
0
1
Order By: Relevance
“…Different peptides reported in scorpion venoms show an amphipathic α-helical structure, like those reported for different cationic antimicrobial molecules [15,16,17,18,19,20,21,22,23]. These peptides, show hemolytic, immune modulating, antibacterial, and insecticidal activities [1,23,24].…”
Section: Introductionmentioning
confidence: 96%
“…Different peptides reported in scorpion venoms show an amphipathic α-helical structure, like those reported for different cationic antimicrobial molecules [15,16,17,18,19,20,21,22,23]. These peptides, show hemolytic, immune modulating, antibacterial, and insecticidal activities [1,23,24].…”
Section: Introductionmentioning
confidence: 96%
“…High-resolution structure of Pin2, determined by NMR, showed that the peptide is essentially alpha-helical with a proline, which induces a structural “ kink ” in the central part of its structure [15]. The proline “ kink ” is a structural characteristic of some CAMPs that confer them high pore-forming abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Scorpion venom has been investigated mostly for its neurotoxins acting on different ion channels [1][2][3]. Recently, a-helical pore-forming peptides have been discovered in scorpion venom (parabutoporin [4], hadrurin [5], IsCTs [6,7] and pandinins [8]). In addition, the cDNA sequence of a peptide from Buthus martensii has been described, but biological activity of the peptide has not yet been studied [9].…”
mentioning
confidence: 99%